Konfigurasi Politik Atas Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana - Imam Hakiki; Resti Kurnia (Journal Law and Government, 2024)
This research focuses on examining the character of legal products in the Joko Widodo regime, one of which is Law Number 1 of 2023 concerning the Criminal Code. The problem in this study is that the political situation in a country greatly influences the formation of a law. The research method used in this research is normative legal research that examines legal issues and examines norms, as for what is studied in this study is the character of legal products of Law Number 1 of 2023. This research aims to answer (1) How is the political configuration of the presence of Law Number 1 of 2023 concerning the Criminal Code in law enforcement in Indonesia? (2) What is the character of legal products of Law Number 1 of Year 2023? This research concludes that the political situation can affect the formation of a law. A democratic political configuration will give birth to responsive legal products while an authoritarian configuration will give birth to legal products that are conservative or elitist. In this study, the author assesses Law Number 1 Year 2023 as a responsive legal product, the reform of the Criminal Code is a form of legal development aimed at answering the needs of society.